Systemic enzyme therapy and clinical and hemorheological parameters in coronary heart disease patients with effort angina - A. Yu. Konyakhin; A. E. Radzevich; G. V. Arkadyeva; N. V. Shmeleva; T. R. Kameneva; E. S. Antonova (Российский кардиологический журнал)
This study is devoted to systemic enzyme therapy (wobenzym and phlogenzym) influence on hemostasis, hemorheology, and clinical course of disease inpatients (n=54) with Functional Class II-III effort angina, receiving complex therapy. Systemic enzyme therapy improved blood rheology due to decreased red and white blood cell aggregation, increased elasticity of red blood cell membrane; optimized fibrinolysis and hemocoagulation systems' status; improved angina clinical course and quality of life. Including wobenzym and phlogenzym into complex therapy ofFC II-III effort angina patients is clinically rational, effective, and safe.